79.6k views
5 votes
Girardo is using the model below to solve the equation 3x+1=4x+(-4)​

2 Answers

2 votes

Answer:

x = 5

Explanation:


3x+1=4x+(-4)\qquad\text{subtract}\ 4x\ \text{from both sides}\\\\3x-4x+1=4x-4x-4\\\\-x+1=-4\qquad\text{subtract 1 from both sides}\\\\-x+1-1=-4-1\\\\-x=-5\qquad\text{change the signs}\\\\x=5

User Mehamasum
by
6.4k points
1 vote

Answer:

The answer is B. In step one he should have added 3 negative x-tiles to both sides.

Explanation:

User Michael Bordash
by
5.7k points